Back‐to‐Back Occurrence of Tropical Cyclones in the Arabian Sea During October–November 2015: Causes and Responses. Issue 6 (12th June 2020) - Roy Chowdhury, Riyanka; Prasanna Kumar, S.; Narvekar, Jayu; Chakraborty, Arun
Abstract: In the Arabian Sea, two extremely severe cyclonic storms occurred back to back during October–November 2015. Using a suite of ocean and atmospheric data, we examined the upper ocean responses of tropical cyclones Chapala and Megh, the latter originated immediately after the dissipation of the former. Cyclones Chapala and Megh cooled the sea surface by 1.5°C and 1.0°C, respectively, which was also captured by Bio‐Argo float in the vicinity of their tracks. The cyclone‐induced chlorophyll a enhancement was 6 and 2 times respectively from their precyclone value of 0.36 and 0.30 mg/m 3, while the net primary productivity showed an increase of 5.8 and 1.7 times respectively from the precyclone values of 496.26 and 518.63 mg C/m 2 /day after the passage of Chapala and Megh. The CO2 flux showed a sixfold and twofold increase respectively compared to the precyclone value of 2.69–3.58 and 6.78 mmol/m 2 /day. We show that the anomalous co‐occurrence of the positive phase of Indian Ocean Dipole and the strong El Niño supported large‐scale warming in the western Arabian Sea. Subsequent altered Walker circulation played a decisive role in the preconditioning of both atmosphere and ocean, which led to a situation congenial for cyclogenesis. What triggered the formation of the cyclone Chapala was the arrival of eastward‐propagating atmospheric convection associated with the Madden‐Julian oscillation. The generation of the second cyclone Megh within 8 days appears to be associated with the oceanic Rossby wave that led to an increase in the upper ocean heat content by deepening the 26°C isotherm in the vicinity of the origin of cyclones. Plain Language Summary: The Arabian Sea, situated in the western part of the North Indian Ocean, is prone to cyclones, and it has a profound impact on its biogeochemistry. It is in this context that our study is important as it aims at understanding the response of the back‐to‐back cyclones Chapala and Megh that occurred during October–November 2015, which is a rare phenomenon. Rare because once a cyclone is generated, it utilizes the available heat energy of the upper ocean, and hence, another cyclone cannot be formed immediately in the same region. Through this study, we show that in October–November 2015, an unusual warming occurred in the western Arabian Sea due to a unique co‐occurrence of an ocean‐atmosphere condition that favored the formation of back‐to‐back cyclones. Our study shows that the twin cyclones Chapala and Megh increased the biological productivity of the ocean as well as the emission of CO2 gas from ocean to atmosphere 2 to 6 times. The implication of our result is that if the number of cyclones is going to increase in the future, Arabian Sea will become oxygen deficit, and it will give out more CO2 to the atmosphere, thereby increasing the chance of more warming. Key Points: Cyclone formation consumes upper ocean heat and hence cannot support another one right away, making back‐to‐back‐cyclone occurrence special Preconditioning of ocean‐atmosphere by ENSO‐IOD‐mediated anomalous warming of the western Arabian Sea led to the formation of Chapala and Megh Chlorophyll a and CO2 flux increased by sixfold and twofold, while SST cooled by 1.5°C and 1°C after cyclones Chapala and Megh, respectively